Pengaruh Model Pembelajaran Project Based Learning terhadap Kemampuan Pemecahan Masalah Matematika - Desak Putu Yosi Andini; I. N. Sukajaya; Gede Suweken (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Given that mathematical problem-solving proficiency continues to lag as a persistent concern within Indonesian secondary education, instructional approaches capable of cultivating higher-order thinking skills are urgently called for. This study set out to compare the Project-Based Learning (PjBL) and Problem-Based Learning (PBL) models, examining the effect each had on students' mathematical problem-solving ability. A quantitative quasi-experimental design with a posttest-only control group framed this research, drawing its participants from eighth-grade students at SMP Negeri 2 Banjar who were selected through cluster random sampling. Following normality and homogeneity testing, data collected through a validated essay-based assessment were subjected to analysis via an independent samples t-test. At p = 0.013, the gap between the two groups proved statistically significant, with students exposed to PjBL emerging with the upper hand in mathematical problem-solving performance. These findings suggest that PjBL provides a more meaningful and contextually enriched learning experience, making it a promising pedagogical alternative for strengthening mathematical problem-solving competencies in junior high school settings.